Multiple sex chromosome systems in howler monkeys (Platyrrhini, Alouatta) - Eliana Steinberg; Mariela Nieves; Marta Dolores Mudry (Comparative Cytogenetics, 2014)
In light of the multiple sex chromosome systems observed in howler monkeys (Alouatta Lacépède, 1799) a combined cladistic analysis using chromosomal and molecular characters was applied to discuss the possible origin of these systems. Mesoamerican and South American howlers were karyologically compared. FISH analysis using the chromosome painting probes for the #3 and #15 human chromosomes was applied to corroborate the homeology of the sexual systems. We found that the HSA3/15 syntenic association, present in the sex chromosome systems of South American Howlers, is not present in those of Mesoamerican ones. The autosomes involved in the translocation that formed the sexual systems in the Mesoamerican and South American species are different, thus suggesting an independent origin. Parsimony analysis resolved the phylogenetic relationships among howler species, demonstrating utility of the combined approach. A hypothesis for the origin of the multiple sex chromosome systems for the genus is proposed.